Extensions and Applications of Locally Solid Convergence Structures - Saeed Hashemi Sababe (Mathematics)
Locally solid convergence structures provide a unifying framework for both topological and non-topological convergences in vector lattice theory. In this paper, we explore various extensions and applications of locally solid convergence structures. We characterize unbounded locally solid convergences in different spaces, establish connections with bornological convergences, and investigate their applications in functional analysis. Additionally, we generalize these structures to non-Archimedean vector lattices and compare them with traditional topological frameworks. Finally, we develop applications in fixed point theory and operator spaces. Our results contribute to a deeper understanding of the interplay between different types of convergence structures in mathematical analysis.